PENANGAN JENAZAH TIDAK UTUH DALAM SITUASI DARURAT: ANALISIS PERSEPEKTIF HUKUM ISLAM DAN SAINS FORENSIK - Taufiq; Rahmat Hidayat; Irwan (Yayasan Baitul Hikmah al-Zain, 2026)
The handling of incomplete corpses in emergency situations presents a complex issue, considering the importance of respecting the deceased in Islam and the challenges faced in emergency conditions such as natural disasters or accidents. This study aims to analyze the handling of incomplete corpses from the perspectives of Islamic law and forensic science. Specifically, this research examines Islamic legal provisions regarding the burial of incomplete corpses and discusses the dilemmas that arise in emergency situations, such as time constraints and the condition of the body. On the other hand, forensic science provides technical guidelines for identifying incomplete corpses and the procedures required to ensure the deceased's rights are respected, such as forensic analysis to recognize the identity of the deceased and further investigation. The research method used is a qualitative approach with an in-depth literature review on Islamic law related to corpse handling in emergency conditions, as well as the application of forensic principles in handling incomplete corpses. The findings show that although Islamic law regulates corpse handling in detail, in emergency situations, the procedures can be adjusted according to the principle of public welfare without diminishing the obligation to respect the deceased. In the context of forensic science, identification of incomplete corpses can still be performed using appropriate techniques, although standard procedures may not be fully applicable.